Urgensi Penerapan WBS Pada Perusahaan di Indonesia - Gracia Maydelin Arganto (Universitas Kapuas, 2024)
Conflicts arise in companies when individual and company interests differ. Indonesia is fourth globally in fraud cases. This writing suggests to the government the importance of using the Work Breakdown Structure (WBS) in companies, similar to the U.S. The research method is qualitative, utilizing a Comparative Approach and Conceptual Approach. Reaviling a lack of WBS regulations for private companies in Indonesia. The hope is for the government to consider U.S. Sarbanes-Oxley Act for WBS guidelines and whistleblower protection to encourage reporting fraud in companies.